Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1152/ajpgi.90260.2008
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous ghrelin and 5-HT regulate interdigestive gastrointestinal contractions in conscious rats

Abstract: Endogenous ghrelin causes interdigestive contractions of the stomach in rats. In contrast, previous studies showed that 5-HT3 and 5-HT4 receptors were involved in regulating intestinal interdigestive contractions. We studied the possible role of endogenous ghrelin and 5-HT regulating interdigestive gastrointestinal (GI) contractions in rats. Four strain gauge transducers were implanted on the antrum, duodenum, and proximal and distal jejunum. After an overnight fast, GI contractions were recorded in freely mov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 59 publications
(97 reference statements)
1
28
0
Order By: Relevance
“…Our recent study showed that phase Ⅲ-like contractions at the jejunum, not the antrum and duodenum, were significantly attenuated by 5-HT 4 antagonists. In contrast, 5-HT 3 antagonists did not affect phase Ⅲ-like contractions in all of upper GI tract [11] . These suggest that spontaneous phase Ⅲ-like contractions at the jejunum is mediated via 5-HT 4 receptors, but not 5-HT 3 receptors.…”
Section: Introductionmentioning
confidence: 65%
See 3 more Smart Citations
“…Our recent study showed that phase Ⅲ-like contractions at the jejunum, not the antrum and duodenum, were significantly attenuated by 5-HT 4 antagonists. In contrast, 5-HT 3 antagonists did not affect phase Ⅲ-like contractions in all of upper GI tract [11] . These suggest that spontaneous phase Ⅲ-like contractions at the jejunum is mediated via 5-HT 4 receptors, but not 5-HT 3 receptors.…”
Section: Introductionmentioning
confidence: 65%
“…Previous report showed that ghrelin stimulates motility in the rat small intestine and that the stimulatory effect of ghrelin is mediated via cholinergic neurons of the myenteric plexus [12] . Our recent study showed that GHS-R antagonists inhibited phase Ⅲ-like contractions at the antrum, but not the duodenum and the jejunum [11] . Previous studies also showed that GHS-R antagonists did not affect phase Ⅲ-like contractions in the duodenum [8] .…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Under the dissecting microscope, the lower part of the esophagus was exposed and anterior and posterior branches of the vagal nerves were incised above the hepatic and celiac branches, as previously reported [15] . In sham operation rats, the vagal trunks were similarly exposed but not cut [16] .…”
Section: Animal Surgerymentioning
confidence: 99%